The tough process of unmasking the slow-growing mycobacterium: case report of Mycobacterium microti infection. Issue 1 (31st January 2020) - van de Weg, Cornelia A. M.; de Steenwinkel, Jurriaan E. M.; Miedema, Jelle R.; Bakker, Marleen; van Ingen, Jakko; Hoefsloot, Wouter
Abstract : Mycobacterium microti belongs to the Mycobacterium tuberculosis complex (MTBC). It can cause pulmonary and extrapulmonary tuberculosis in humans. Compared to M. tuberculosis, which is the most prevalent subspecies of the MTBC, M. microti infection has a different etiology. Moreover, establishing the diagnosis with conventional bacteriology can be difficult. We will illustrate this with a case of an extrapulmonary tuberculosis of the hip caused by M .microti in an immunocompetent patient in The Netherlands.